Brigham Young's homes - Whitley, Colleen, 1940-; Brimhall, Sandra Dawn, 1953- (Utah State University Press, 2002)
This collection surveys the many houses, residences, farms, and properties of Brigham Young, leader of the Mormon pioneers, first territorial governor of Utah, and second president of the Church of Jesus Christ of Latter-day Saints. The authors discuss, in addition to the buildings themselves, what went on within their walls, looking especially at the lives of Young's plural wives and their children. Their emphasis is on Young's residences as homes, not just structures. The text is heavily illustrated with photos, drawings and maps.